2019
DOI: 10.1096/fj.201900559r
|View full text |Cite
|
Sign up to set email alerts
|

Human glycan expression patterns influence Group A streptococcal colonization of epithelial cells

Abstract: Colonization of the oropharynx is the initial step in Group A Streptococcus (GAS) pharyngeal infection. We have previously reported that the highly virulent M1T1 GAS clone attaches to oral epithelial cells via M1 protein interaction with blood group antigen carbohydrate structures. Here, we have identified that colonization of human oral epithelial cells by GAS serotypes M3 and M12 is mediated by human blood group antigens [ABO(H)] and Lewis (Le) antigen expression. Removal of linkage‐specific fucose, galactos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Interactions of planktonic GAS with a variety of glycan structures have been observed in numerous studies, many of which indicate that host glycans are implicated in GAS binding and adhering to host cells [23][24][25]. In the current study, removal of N-linked glycans from the Detroit 562 pharyngeal cell surface significantly decreased initial adherence of planktonic M12 GAS.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Interactions of planktonic GAS with a variety of glycan structures have been observed in numerous studies, many of which indicate that host glycans are implicated in GAS binding and adhering to host cells [23][24][25]. In the current study, removal of N-linked glycans from the Detroit 562 pharyngeal cell surface significantly decreased initial adherence of planktonic M12 GAS.…”
Section: Discussionsupporting
confidence: 51%
“…The importance of terminal monosaccharides has been demonstrated in a previous study of GAS binding to human buccal epithelial (HBE) cells, whereby expression of terminal galactose and sialic acid residues had significant effects on M1, 3, and 12 associations, whilst terminal fucose and N-acetylgalactosamine were of comparatively lesser dependence of binding for all three GAS M-types. It was suggested that fucose and N-acetylgalactosamine may have a host-protective effect, sterically hindering access to the preferred galactose residues [25]. Many pathogens are known to possess their own suite of glycosidases which they utilize to liberate glycan residues for their own metabolic processes, and moreover, to better access preferred glycan structures for adherence [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ) (De Oliveira et al . 2019 ). The M protein-expressing GAS strains were shown to preferentially associate with HBE cells expressing H-antigen.…”
Section: Introductionmentioning
confidence: 99%